TINJAUAN YURIDIS TINDAK PIDANA TERORISME (Studi Perbandingan Hukum Di Indonesia Dan Australia) - Ida Ayu Putu Ari; Putu Eka Trisna Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2021)
Terrorism is an understanding that aims to influence a group of people to commit acts of terror so that other people feel that their safety is threatened. Terrorism is still a problem that is often discussed in the world. The existence of terrorists is not only a threat to the state of Indonesia but also to one of the neighboring countries, namely Australia, Australia has land that is close to Indonesia in terms of its territory. Comparative law is a scientific process carried out to obtain conclusions from two or more objects owned. Comparison of laws by a country on terrorism issues is usually used as a reference in strengthening the security of the presence of terrorists. Australia is a country whose land territory is close to Indonesia. Australia itself has regulated criminal acts of terrorism and has had regulations related to this since 1995. Australia also has regulations that regulate legal aid. Australia is a federal country that has two jurisdictions, namely a federal state and a state. The research method used is normative juridical, the method is carried out by examining library materials or secondary data related to the issues to be discussed. The core of the study is the rule of law that is used as a norm or rule that applies and is obeyed by everyone in regulating behavior. So, nomative legal research can focus on making an inventory of principles, positive law, legal doctrine, rechtsvending law in concreto, systematics, synchronization, comparative law, and legal history.